HIV drug resistance and HIV transmission risk behaviors among active injection drug users. - Kozal, Michael J; Amico, K Rivet; Chiarella, Jennifer; Cornman, Deborah; Fisher, William; Fisher, Jeffrey; Friedland, Gerald (Journal of acquired immune deficiency syndromes (1999), 2005)
HIV(+) injection drug users in clinical care may harbor and transmit drug-resistant HIV. We performed a retrospective study of HIV drug resistance and risk behavior among HIV(+) injection drug users in care to determine the number of needle-sharing events that involved and the proportion of sharing partners exposed to drug-resistant HIV. Among 180 HIV injection drug users, 55 (31%) reported injecting drugs in the previous month, and 22 of these (40%) shared needles and/or works 148 times with 296 partners, of whom 271 (92%) were thought to be HIV(-) or status unknown. Further, 55 (31%) drug users harbored resistant HIV, including 5 (3% of total) who also shared needles and/or works a total of 27 times with 44 partners (18% of all sharing events and 15% of all exposed partners). A small proportion of injection drug users receiving clinical care engage in injection risk behavior and carry resistant HIV; however, because of multiple partners and needle-sharing events, they expose a substantial number of individuals to drug-resistant HIV. Strategies to reduce injection drug use risk behaviors among patients in clinical care are needed to reduce the transmission of sensitive and resistant HIV.
Keywords: Anti-HIV Agents; Cross-Sectional Studies; Disease Transmission, Infectious; Drug Resistance; Female; HIV; HIV Infections; Humans; Male; Needle Sharing; Retrospective Studies; Risk-Taking; Substance Abuse, Intravenous